2021
DOI: 10.1016/j.omtn.2021.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Diverging targets mediate the pathological role of miR-199a-5p and miR-199a-3p by promoting cardiac hypertrophy and fibrosis

Abstract: MicroRNA-199a-5p (miR-199a-5p) and -3p are enriched in the myocardium, but it is unknown whether miR-199a-5p and -3p are co-expressed in cardiac remodeling and what roles they have in cardiac hypertrophy and fibrosis. We show that miR-199a-5p and -3p are co-upregulated in the mouse and human myocardium with cardiac remodeling and in Ang-II-treated neonatal mouse ventricular cardiomyocytes (NMVCs) and cardiac fibroblasts (CFs). miR-199a-5p and -3p could aggravate cardiac hypertrophy and fibrosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Thirdly, LY294002 is also used to inhibit AKT/eNOS signaling pathway, siRNA‐mediated the knockdown of AKT or eNOS can be added to observe the function of AKT/eNOS signaling pathway. Finally, based on previous studies, other target genes or signaling pathway, such as HIF‐1α, 36 sirtuin 1 (Sirt1), 18 and ERK, p38, and JNK signaling pathways 40 are the direct target genes/pathway of miR‐199a‐5, which is worth exploring whether these genes play a role in the antiferroptosis of miR‐199a‐5 during myocardial OGD/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, LY294002 is also used to inhibit AKT/eNOS signaling pathway, siRNA‐mediated the knockdown of AKT or eNOS can be added to observe the function of AKT/eNOS signaling pathway. Finally, based on previous studies, other target genes or signaling pathway, such as HIF‐1α, 36 sirtuin 1 (Sirt1), 18 and ERK, p38, and JNK signaling pathways 40 are the direct target genes/pathway of miR‐199a‐5, which is worth exploring whether these genes play a role in the antiferroptosis of miR‐199a‐5 during myocardial OGD/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, miR‐199a‐5p attracted growing interest in the field of oncology, such as cervical cancer, non‐small cell lung cancer, and papillary thyroid carcinoma in the last few years 15,16 . Recently, the researches on the involvement of miR‐199a‐5p in the control of cardiac physiology and in the pathogenesis of heart failure have been revealed 17–19 . Various studies found that myocardial miR‐199‐5p levels are increased under cardiac damage, which is responsible for pathophysiological alterations contributing to the development of heart diseases including myocardial I/R injury 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forkhead box C2 (Foxc2) participates in blood and lymphatic vessel development as well as regulating adipose cell metabolism [ 351 ]. This transcription factor is a predicted target of miR-199a-5p, a microRNA which has been implicated in cardiac remodeling regulation and ventricular hypertrophy [ 352 ]. In varicose vein tissues, the downregulation of this microRNA may promote vascular smooth muscle cells (VSMC) proliferation by upregulating Foxc2 [ 353 ].…”
Section: Post-transcriptional Control Of Aortic Arch Development By N...mentioning
confidence: 99%
“…The roles of miR-Let7i ( 32 ), miR-1954 ( 33 ), miR-378 ( 34 ), miR-221/222 ( 35 ), miR-199a ( 36 ), miR-99b-3p ( 37 ), miR-125b ( 38 ), and miR130a ( 39 ) in cardiac fibrosis are displayed in Table 1 .…”
Section: Non-coding Rnas In Cardiac Fibrosismentioning
confidence: 99%